2024
DOI: 10.1021/acs.langmuir.3c03339
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals and Applications of Surface Wetting

Tejaswi Josyula,
Laxman Kumar Malla,
Tibin M. Thomas
et al.

Abstract: In an era defined by an insatiable thirst for sustainable energy solutions, responsible water management, and cutting-edge lab-on-a-chip diagnostics, surface wettability plays a pivotal role in these fields. The seamless integration of fundamental research and the following demonstration of applications on these groundbreaking technologies hinges on manipulating fluid through surface wettability, significantly optimizing performance, enhancing efficiency, and advancing overall sustainability. This Review explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 389 publications
(666 reference statements)
0
0
0
Order By: Relevance
“…The Namib Desert beetle relies on a hydrophilic bulge on its back and a hydrophobic waxy surface to collect water from fog . It is found that the spontaneous transport behavior of droplets depends on the wettability and geometric asymmetry gradient of the organism surface, and advanced functional surfaces could be designed accordingly. , …”
Section: Introductionmentioning
confidence: 99%
“…The Namib Desert beetle relies on a hydrophilic bulge on its back and a hydrophobic waxy surface to collect water from fog . It is found that the spontaneous transport behavior of droplets depends on the wettability and geometric asymmetry gradient of the organism surface, and advanced functional surfaces could be designed accordingly. , …”
Section: Introductionmentioning
confidence: 99%